Experimental investigation on the performance and emissions characteristics of ethanol/diesel dual-fuel combustion. (15th May 2018) - Lee, Jeongwoo; Lee, Sunyoup; Lee, Seokhwan
Highlights: Dual-fuel combustion with two direct injectors was investigated. The effects of various ethanol fractions and diesel injection timings were verified. The characteristics of energy fractions were analyzed. The characteristics of combustion duration were analyzed. Abstract: The diesel compression ignition (CI) engine has higher durability and thermal efficiency than the gasoline spark ignition (SI) engine. However, the high levels of nitrogen oxides (NOx) and particulate matter (PM) emissions are major problems of diesel engines due to the auto-ignition of heterogeneous mixtures. The dual-fuel combustion concept could be solution to environmental concerns. Dual-fuel combustion can be implemented by substituting some of the diesel fuel with high-volatility fuels, such as gasoline and natural gas. The premixed mixture condition can be improved to diminish localized rich and stoichiometric regions. Notably, ethanol has greater potential to reduce PM emissions because it is highly volatile and readily oxidized. For these reasons, in this research, the effects of varying the ethanol substitution ratio on engine performance and emissions under the dual-fuel combustion condition were experimentally investigated under various load conditions. The test engine was a heavy-duty single-cylinder diesel engine with two direct injectors. Engine speed was fixed at 1000 rpm and the load condition was varied for an indicated mean effective pressure (IMEP) ranging from 0.2 to 0.8 MPa. The ratio of ethanol to the total input energy was controlled from zero to nearly 50% of the input energy. The NOx and PM emissions decreased with increasing ethanol substitution and the mean size of the PM emissions decreased. For the mid-load condition (IMEP 0.6 MPa), the substitution was increased to 63%, but for low and high loads, higher ethanol fractions could not be used because of insufficient ignition energy at low loads and sharp increment of the in-cylinder pressure under high loads.